2009
DOI: 10.1089/met.2009.0027
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants of theENPP1/PC-1Gene Are Associated With Hypertriglyceridemia in Male Subjects

Abstract: Background: Hypertriglyceridemia is associated with insulin resistance, type 2 diabetes, and the metabolic syndrome. Membrane glycoprotein PC-1 (also termed ENPP1) is a direct insulin receptor inhibitor, and certain polymorphisms of the ENPP1/PC-1 gene have been associated with insulin resistance, type 2 diabetes, obesity, and diabetic complications. Methods:We examined the effect of 3 ENPP1/PC-1 variants (K121Q, rs1044498, and IVS20delT-11, rs1799774, and A→G+1044TGA, rs7754561) on plasma triglyceride levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Among MetS individuals carrying the KQ/QQ genotype, higher values of TG and insulin resistance reflected by HOMA-IR indicated insulin resistance in MetS patients. Recently, a study has demonstrated that the ENPP1 gene polymorphism is associated with hypertriglyceridemia and may contribute to insulin resistance or MetS [37]. Our results are similar to those of a vast majority of studies carried out in different populations.…”
Section: Discussionsupporting
confidence: 89%
“…Among MetS individuals carrying the KQ/QQ genotype, higher values of TG and insulin resistance reflected by HOMA-IR indicated insulin resistance in MetS patients. Recently, a study has demonstrated that the ENPP1 gene polymorphism is associated with hypertriglyceridemia and may contribute to insulin resistance or MetS [37]. Our results are similar to those of a vast majority of studies carried out in different populations.…”
Section: Discussionsupporting
confidence: 89%
“…Multiple linkage studies have associated the chromosome locus mapping ENPP1, to insulin resistance [90,93,94], hyperglyceridaemia [95], childhood and adult obesity and increased risk of type 2 diabetes [8]. Furthermore, specific polymorphisms have been identified, of which Lys121Gln (K121Q) [96] is the most widely investigated.…”
Section: Insulin Signalling and Glucose Homeostasismentioning
confidence: 99%
“…[6][7][8][9] ENPP1 lies on chromosome 6q22-q23 (OMIM#173335) in a region where several independent studies found a linkage peak to OB phenotypes. [10][11][12][13] ENPP1 is an attractive candidate gene for studying OB, as it was proposed as a key player in the etiology of insulin resistance 14,15 and in a recently suggested mechanism underlying defective adipocyte maturation. 16 The ENPP1 product has also been identified as one of the central regulators of extracellular pyrophosphate (ePPi)/phosphate (Pi) equilibrium levels.…”
Section: Introductionmentioning
confidence: 99%